lncRNA LINC00460 Silencing Represses EMT in Colon Cancer through Downregulation of ANXA2 via Upregulating miR-433-3p - Weiwen Hong; Hongan Ying; Feng Lin; Ruliang Ding; Weiya Wang; Meng Zhang (Elsevier, 2020)
Colon cancer (CC), one of the major causes of tumor-associated death, is often presented with a heterogenic pool of cells with unique differentiation patterns. This study explored the functions that LINC00460 displayed in CC by regulating microRNA-433-3p (miR-433-3p) and Annexin A2 (ANXA2). LINC00460 expression was either silenced or overexpressed in HCT-116 and LOVO cells to explore the functional roles of LINC00460 in CC. The relationship between miR-433-3p and LINC00460/ANXA2 was analyzed using dual-luciferase reporter assay, RNA-pull down, and RNA immunoprecipitation (RIP) assays. Cell proliferation, metastasis, invasion, and apoptosis were examined in vitro, and tumorigenicity was evaluated in vivo following LINC00460 silencing. Additionally, the regulatory mechanisms were investigated using LINC00460 and ANXA2 gain- or loss-of-function experiments. We found that LINC00460 was expressed highly in CC. Downregulation of LINC00460 inhibited cell invasion and proliferation in vitro and restrained tumor growth in vivo. Moreover, LINC00460 was able to specifically bind to miR-433-3p to increase the expression of ANXA2. Furthermore, LINC00460 downregulated the E-cadherin expression and upregulated the vimentin and N-cadherin expression by upregulating ANXA2, therefore inducing epithelial-mesenchymal transition. These findings suggested that LINC00460 might function as an oncogenic long non-coding RNA (lncRNA) in CC development and could be explored as a potential biomarker and therapeutic target for CC. Keywords: long non-coding RNA, LINC00460, competing endogenous RNA, microRNA-433-3p, Annexin A2, colon cancer, cell invasion, cell proliferation, cell metastasis, xenograft tumor in nude mice